Trichuriasis among Orang Asli children at Pos Lenjang, Pahang, Malaysia - Hartini Yusof; Mohamed Kamelabd Ghani (penerbit ukm, 2012)
A cross-sectional study was conducted in February 2006 to determine the prevalence of Trichuris trichiura infection among Orang Asli (Aborigine) children at Pos Lenjang, Pahang. A total of 71 faecal samples were collected from the children (40 girls and 31 boys) aged between 1-12 years. The samples were examined for the presence of Trichuris trichiura ova using direct smear and formalin-ether concentration techniques. The result revealed that the overall prevalence of Trichuris trichiura infection was 43.7%. The infection was higher in males (51.6%) compared to females (37.5%), though not statistically significant (p > 0.05). According to age group, the school-aged children had higher prevalence of infection (56.8%) than preschool children (29.4%) (p < 0.05). Low socioeconomic status, large family size, poor environmental sanitation and poor personal hygiene are possible contributing factors that increase the prevalence of infection among the Orang Asli children at Pos Lenjang. In 31 samples positive for Trichuris trichiura, a detection rate of 100% was obtained using formalin-ether concentration, compared to 25.8% with direct smear technique. Thus, it is recommended that both techniques be performed in routine faecal examination for a more accurate diagnosis.